A diagrammatic hand-sewing sourcebook for the enhanced instruction and learning of beginning sewers. - Lapena, Jessica G. (2013)
Sewing is a skill that is often overlooked, especially in today's urban setting. It is easy to have repairs done by professionals, or to buy ready-to-wear clothing, and many would say that they don't have time to sew. But those who are genuinely interested iin learning how to sew, whether for practical or creative purposes, are likely to find the time to. The problem of how to learn is another story - one that I have found is best told visually. Instructional diagrams, which present a simplified version of procedures like sewing, are an ideal way to learn such skills that cannot be conveyed through words alone. Thus sewing, which deals with physical materials and procedures, is best learned visually. Hubel and Wiesel's visual cues (color, form, movement and depth), which are the four most effective stimuli of the brain's visual processing unit, should add to the impact and effectiveness of these diagrams, while also providing a scientific foundation for an artist's speculation. In order to test the effectiveness of diagrams against verbal instructions (which are commonly seen in sewing modules and books), I devised an experiment for intermediate-level students using three types of instructional materials: one, purely verbal, the other purely diagrams, and the third, a combination of words and pictures. The pilot test subjects were 13-15 year-old students from the UP Integrated school, both male and female. The thirty-one students were discreetly divided into three groups and administered the different sets of handouts together with the materials for executing three hand stitches: overcasting, herring-bone and Cretan leaf stitch. The results showed that there was not much a difference between groups, although the work of the second set of students (those that received purely visual instructions) was relatively more evenly scored at a satisfactory level, while the first set (those that received purely verbal instructions) showed erratic results and the third, which received a combination of visual and verbal instructions, showed significantly lower scores.